Neuromuscular Adaptations to Constant vs. Variable Resistance Training in Older Men - Walker, S.; Peltonen, H.; Sautel, J.; Scaramella, C.; Kraemer, W. J.; Avela, J.; Häkkinen, K. (International Journal of Sports Medicine, 2014)
This study examined the effects of constant or variable external resistance training on neuromuscular adaptations in the lower limbs of older men. 37 subjects (age 65±4 year) were quasi-randomly assigned to the constant or variable training group, or a non-training control group. Training consisted of a 20-week medium-intensity, high volume resistance training program. Maximum bilateral concentric and isometric force production of the leg extensors as well as repetitions-to-failure test were performed pre-, mid- and post-training. Vastus lateralis muscle cross-sectional area was assessed by ultrasound and lean leg mass was assessed by dual-energy x-ray absorptiometry. Both training groups significantly increased force production of the leg extensors (variable: 26 kg, 95% CI=12–39, P<0.01; constant: 31 kg, 95% CI=19–43, P<0.01) and VL cross-sectional area (variable: 1.5 cm2, 95% CI=0.03–3.1, P=0.046; constant: 3 cm2, 95% CI=1.2–4.8, P=0.002). However, only the variable training group significantly improved repetitions to failure performance (704 kg, 95% CI=45–1 364, P=0.035). Only the variable resistance training group improved fatigue-resistance properties, which may be an important adaptation to maintain exercise and functional capacity in older individuals.
Keywords: force production; hypertrophy; neural adaptation; quadriceps